Caracterização experimental do escoamento bifásico horizontal de fluidos reofluidificantes - Baungartner, Rafael (2017)
Investigate the local and global properties of a horizontal gas-liquid slug flow, in three different shear-thinning fluids. To do so, an experimental testing bench was assembled and validated using an air-water slug flow. Three different working fluids where prepared to be used in the testing section, where an extensive experimental measurement campaign was carried out. The main characteristics of the biphasic flow, such as bubbles length and velocity, slug length and aeration level where measured with a high speed camera through Shadow Sizer technic. The velocity field of the liquid phase was measured using Particle Image Velocimetry (PIV). The fluids rheological properties where quantified using a rotational rheometer in the beginning and at the end of each experiment. In addition, to each test, the pressure distribution was measured through the 12m long acrilic pipe, varying the gas and liquids flow rates. All this properties of liquid and gas phases where quantified for three gas and liquid flow rates, totalizing 9 different conditions for each fluid. Properties of the monophasic liquid flow where also evaluated for all fluids. The main objective of this work is to analyze the influence of liquid phase rheological characteristics in slug flow behavior. The experimental results will be used to validate literature modifications to the mechanistic models used in slug flow local and global properties prediction.